Studies on pulsed Nd:YAG laser cutting of thick stainless steel in dry air and underwater environment for dismantling applications. (August 2015) - Choubey, Ambar; Jain, R.K.; Ali, Sabir; Singh, Ravindra; Vishwakarma, S.C.; Agrawal, D.K.; Arya, R.; Kaul, R.; Upadhyaya, B.N.; Oak, S.M.
Abstract: Dismantling of old equipments and structures is an important application in nuclear facilities and shipping industry. This paper presents a study on process optimization during pulsed Nd:YAG laser cutting of thick stainless steel (AISI SS304) sheets having a thickness in the range of 4–20 mm in dry air and underwater environment. Laser cutting experiments have been performed using a 500 W average power long pulse Nd:YAG laser system with fiber optic beam delivery. A water shielded laser cutting nozzle with coaxial gas jet was specifically developed to form a local dry cavity around the laser beam during the cutting experiments in underwater condition. It was found that for a given pulse energy, a higher cutting speed is possible with optimal value of pulse duration, spot overlapping, and assist gas pressure. Cutting speed of 20 mm thick SS sample was enhanced to about three times by means of increase in pulse duration from 14 ms to 20 ms and reduction in the required spot overlapping from a value of 80% to 40% using oxygen as the assist gas. A comparison of the cutting speed and heat affected zone in dry air and underwater environment has been performed. These results will be highly useful in laser based dismantling of old steel structures in radioactive and underwater environment to save time and minimize radiation dose consumption as compared to conventional dismantling methods. Highlights: A study on pulsed Nd:YAG laser cutting of thick SS in dry air and underwater. Cutting speed has been enhanced using optimized value of pulse duration, spot overlapping, and assist gas pressure. These results useful for dismantling work in radioactive and underwater environment.